Attributes and Activities of Religious Communities in Italy: First Results from a City Congregations Study (CCS) - Breskaja, Olʹga Jurʹevna (Religions, 2023)
This article explores the attributes and religious, social and political activities of local religious groups in three Italian cities across all religious traditions. This is the first application of Congregations Study methodology in Italy to analyze the social composition, structure and activities of religious communities. The research was conducted between 2020 and 2021 with a total number of 877 communities mapped in the cities of Bologna, Milan and Brescia, and their surroundings. All local religious groups in three cities and their surroundings were counted and one key informant per group was interviewed (N = 566) with a Congregations Study questionnaire. Based on the results of the interviews, we found that, during the last decade, the dynamics of growth of adults’ and children’s regular religious participation was distinct within the Muslim and Christian Orthodox communities. Social service for elderly, environmental programs and political activity were found to be promoted by the Catholic communities to a stronger degree, while activities linked to the support of migrants were endorsed stronger by Muslim and Orthodox groups. Moreover, this study assessed the theological, ethical and political orientation of religious communities, highlighting different trends across religious traditions. The article discusses various configurations of urban religious diversity by bringing similarities and contrasts between communities of dominant religious tradition and minority religions, thus questioning the applicability of City Congregations Study (CCS) methodology to the analysis of configurations of religious diversity in Italy.